2016
DOI: 10.4067/s0034-98872016001100003
|View full text |Cite
|
Sign up to set email alerts
|

Predictores clínicos y funcionales del riesgo de cáncer pulmonar en el seguimiento de una cohorte de adultos fumadores

Abstract: Background: Identifying risk factors for lung cancer in the population could improve the cost-effectiveness of early detection programs using thoracic computed tomography (CT (Rev Med Chile 2016; 144: 1382-1390

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In our study, the mean age of patients in the CHM cohort was significantly older than those in the non-CHM cohort (57.7 years vs 55.9 years; p < 0.001). Statistical analyses have indicated that age is an independent risk factor for lung cancer, particularly age above 60 years (Saldias Penafiel et al, 2016; Sandelin et al, 2018). These findings are consistent with our study data; older age was positively correlated with the risk of lung cancer ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the mean age of patients in the CHM cohort was significantly older than those in the non-CHM cohort (57.7 years vs 55.9 years; p < 0.001). Statistical analyses have indicated that age is an independent risk factor for lung cancer, particularly age above 60 years (Saldias Penafiel et al, 2016; Sandelin et al, 2018). These findings are consistent with our study data; older age was positively correlated with the risk of lung cancer ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Smoking is one of the most significant pathogenic factors of male lung cancer [4,5]. This habit is also associated with eye diseases like hyperopia, delayed corneal epithelial healing, progression of Fuchs' endothelial corneal dystrophy, age-related nuclear cataract, retinal diseases, uveitis, optic neuropathies, and thyroid-associated orbitopathy [6].…”
Section: Introductionmentioning
confidence: 99%
“… 8 9 Information regarding pack-years has been widely used to assess the risks of lung cancer and chronic obstructive pulmonary disease (COPD). 10 11 Pack-years of smoking is calculated by multiplying the number of packs of cigarettes smoked per day by the number of years the person has smoked. The total number of base substitution mutations is positively correlated with pack-years smoked for all cancer types; based on these correlation rates, it is estimated that the approximate number of mutations accumulated in a normal cell of each tissue due to smoking a pack of cigarettes per day for a year is 150, particularly in the lungs.…”
Section: Introductionmentioning
confidence: 99%